Plan de negocios comercializadora de hierbas aromáticas tipo exportación (2022)
The business plan for marketing aromatic herbs for export was proposed as an alternative to meet the exponential growth in demand for aromatic herbs in the US market, analyzing the different legal and compliance requirements to carry out the export of perishable products. a market study and geographical strategic analysis that allows the proper development of the activity, possible suppliers and quality analysis of the products offered and part of the organizational and structural culture that is required was determined. Within the financial analysis, all the necessary working capital that is required was determined, taking into account one of the main benefits that is sought to be obtained, which is to prioritize employment for people who are victims of violence and the armed conflict, the initial investment with financial entities as well as the estimation of costs and interests, property, plant and equipment for the area of production and maquila, sales and administration, direct and indirect costs in the production, administrative and sales process, main products to be marketed, detailing the product more sold and its profitability, cost benefit and break-even point. As the last part of the development of the work, the respective financial statements were issued, projected of 6 months, showing the expected profitability and viability of the business